2017
DOI: 10.1039/c6cc08396j
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between π-conjugated chromophores in a giant molecular spoked wheel

Abstract: We discuss the intriguing photophysics of a giant molecular spoked wheel of π-conjugated arylene-alkynylene chromophores on the single-molecule level. This "molecular mesoscopic" structure, CH, shows fast switching between the 12 identical chromophores since the fluorescence is unpolarised but only one chromophore emits at a time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…As such, the self-assembly of such spoked wheels on surface could be further controlled with different patterns and symmetries. [127][128][129][130][131] Compared to the structure of hollow-centered macrocycles, the rigidity of spoked wheel was highly improved. However, it was found that the spoked wheels based on poly(p-phenylene ethynylene)s decomposed slowly at room temperature.…”
Section: Spoked Wheelsmentioning
confidence: 99%
“…As such, the self-assembly of such spoked wheels on surface could be further controlled with different patterns and symmetries. [127][128][129][130][131] Compared to the structure of hollow-centered macrocycles, the rigidity of spoked wheel was highly improved. However, it was found that the spoked wheels based on poly(p-phenylene ethynylene)s decomposed slowly at room temperature.…”
Section: Spoked Wheelsmentioning
confidence: 99%
“…Resulting from weak non-covalent intermolecular interactions, supramolecular assemblies enable the growth of well-extended and highly-ordered structures with tunable chemical, optochemical or mechanical properties [9][10][11][12][13] . In aqueous environments, extended polycyclic hydrocarbon molecule (PAH) assemblies have been also reported through the interdigitation of long alkyl chains [14][15][16][17][18] . While these organic architectures have already shown potential applications in photovoltaics and nanoelectronics 19 , the weak intermolecular interactions governing these assemblies and the intrinsic flexibility of the precursors also offer new opportunities for the design of responsive materials to external stimuli 6,20 .…”
mentioning
confidence: 99%
“…This approach, however, limits the size of the precursors and prevents the use of fragile moieties such as long alkyl chains that might degrade during evaporation. In liquid, such size or composition limitations are not present 11,[13][14][15][16][17][18] . In UHV conditions, the electrospray deposition (ESD) technique allows the introduction of large molecules.…”
mentioning
confidence: 99%